Premenstrual syndrome: influences in the nursing team of surgical centers - De Mattia, Ana Lúcia; Telles, Bruna; Madureira Santos, Carla Affonso; Castello Bernauer, Maura (O Mundo da Saúde, 2008)
This is a descriptive and exploratory study with a quantitative method using an analysis of data in terms of absolute and relative frequency. It aims to identify signals of premenstrual syndrome of nursing teams and verify whether these interfere in the adequate performance of work tasks. The research was carried out with 30 hardworking women of the Surgical Center of big Private Hospital of Santos city. A form was applied containing 15 structured questions. Most study subjects had from 28 to 32 years of age and were trained as nursing assistants. From the investigated symptoms, breasts intumescing was the most frequent, followed by a weight sensation in the pelvis, abdominal pains and irritability; most subjects had more than 5 signals and symptoms of premenstrual syndrome, problems that do not influence absence from work: 26 (87.0%) of the sample did work in spite of this. Thus, the research identified symptoms of premenstrual syndrome, but these do not interfere in the adequate professional performance.